DRIVING ORGANIZATIONAL TRANSFORMATION BY LEVERAGING LEAN TO OPTIMIZE EFFICIENCY: A PEOPLE, CULTURE, AND SYSTEM APPROACH AT A PRINTING COMPANY IN INDONESIA - Permana, Iman; Ginting, Valentina Boru (President University, 2024)
The manufacturing industry has undergone a remarkable transformation in recent years, driven by the increasing demand for high-quality products that can be delivered quickly and efficiently. This change results from the growing demand for high-quality goods that can be delivered promptly and effectively. Manufacturers are under tremendous pressure to increase operational effectiveness, cut production costs, react quickly to consumer demands, and preserve a competitive edge as the world's marketplaces become more competitive Lean manufacturing has become a potent methodology for achieving operational excellence and fostering continuous improvement within firms as a response to these difficulties. Lean manufacturing has been widely adopted and is beneficial in reducing non-value-added activities and waste in both the industrial and service sectors. Over processing, overproduction, high inventory, waiting times for personnel or materials, motion, defects, and wasteful transportation are the seven waste categories recognized by lean manufacturing. Due to their emphasis on achieving zero waste and adding value for customers, lean management approaches have become well-known on a global scale. According to earlier studies, successfully implementing lean practices provides substantial advantages, such as waste reduction, cost savings, enhanced quality, increased customer satisfaction, and improved efficiency.However, implementing lean practices has been a challenging journey for many organizations, with the desired results often being more attainable organizations confront challenges in fully optimizing their implementation. Despite the benefits associated with lean manufacturing, a phenomenon exists wherein numerous businesses need help to adapt to and sustain lean principles, resulting in only about 10% of companies effectively adopting a lean manufacturing approach. Lean practice implementation is a complex process that depends on several key success factors.PT XXX, which operates within the packaging and printing industries, has implemented Lean principles to enhance organizational efficiency. However, the current implementation of Lean at PT XXX is encountering difficulties in realizing its intended objectives. This challenge is evident through the persistent existence of non-value-added activities within the organization, consuming valuable resources such as time, effort, and materials, yet failing to contribute value to the final product and customer satisfaction. This also correlates with an increasing number of customer complaints. In 2020, there were 48 customer complaints; in 2021, there were 59 customer complaints; and in 2022, there was a significant increase of about 95% compared to the previous year. This indicates that the implementation may still need to be optimized.This research investigates lean practices within PT XXX its focus is on uncovering the factors influencing the optimization of lean processes, and driving operational efficiency. One of the approaches is Human Resource Management principles. The research delves into the impacts of people participation, organizational culture, and an effective system. By examining these aspects, the study provides valuable insights for businesses aiming to refine their lean methodologies to increase the efficiency of the organization. Utilizing a quantitative approach, this study involved a total of 250 respondents as the samples, selected based on the Slovin formula. The data were analyzed using Microsoft Excel, SPSS v.26, and SmartPLS 4.0 tools with the PLS-SEM analysis method. The study found the positive influence of people, culture, and systems in optimizing lean implementation. Firstly, engaging people as active participants is pivotal for successful lean implementation, fostering a culture of continuous improvement. Secondly, a supportive organizational culture is crucial for sustaining lean transformation through collaborative environments and ongoing improvement efforts. Thirdly, effective systems and processes, including integrating KPIs aligned with strategic goals, promote visibility and accountability, facilitating continuous improvement). Lastly, implementing Lean principles effectively reshapes organizational operations and culture, enhancing efficiency and quality. Organizations can enhance lean implementation by focusing on key strategies. This finding highlights the fundamental role of human capital in driving organizational improvement through lean principles. The result of this study can guide PT XXX and other similar organizations towards optimized lean implementation, fostering a culture of continuous improvement and achieving enhanced operational performance in the dynamic landscape of modern manufacturing.